2003
DOI: 10.1007/s00540-003-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid improvement of respiratory symptoms associated with fat embolism by high-dose methylpredonisolone: a case report

Abstract: The patient manifested mild hemoptysis 2 days after the admission; however, other symptoms of respiratory failure were not observed. Although preoperative laboratory values showed mild anemia (hemoglobin, 9.5 g·dl Ϫ1 ; hematocrit, 29.8%) and thrombocytopenia (95 000 · mm Ϫ3 ), the patient's general condition was considered acceptable for right hip arthroplasty under general anesthesia to be undertaken. Prior to induction of anesthesia, a 22-gauge cannula was inserted into the left radial artery for monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…[252] Prophylactic corticosteroids have been shown to reduce the risk of FES in high risk patients. A recent meta-analysis of six randomized trials (389 patients with long-bone fractures) comparing systemic corticosteroids plus supportive care to supportive care alone has demonstrated reduced incidence of FES without any positive influence on mortality[53] However, further studies have been advised to conclusively ascertain the role of steroids. [54] None of our patients received steroids.…”
Section: Discussionmentioning
confidence: 99%
“…[252] Prophylactic corticosteroids have been shown to reduce the risk of FES in high risk patients. A recent meta-analysis of six randomized trials (389 patients with long-bone fractures) comparing systemic corticosteroids plus supportive care to supportive care alone has demonstrated reduced incidence of FES without any positive influence on mortality[53] However, further studies have been advised to conclusively ascertain the role of steroids. [54] None of our patients received steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting beneficial effects used doses of methyl prednisolone between 9 mg/kg and 90 mg/kg (in divided doses). The results of these trials were impressive, with a 10-fold reduction of FES in one series (Stoltenberg and Gustilo, 1979; Kubota et al, 2003).…”
Section: Treatmentmentioning
confidence: 99%
“…Several studies have shown that early mobilization and prophylactic corticosteroid therapy in trauma patients to be at least moderately effective in reducing the incidence of pulmonary fat embolism. [22][23][24][25][26][27] Schonfeld et al performed a randomized controlled trial in 64 patients with lower-extremity long-bone fractures. 11 Fat embolism was diagnosed in 22% of patients exposed to placebo versus none in the steroid-treated arm.…”
Section: Discussionmentioning
confidence: 99%